1999
DOI: 10.1192/pb.23.11.667
|View full text |Cite
|
Sign up to set email alerts
|

Perceived role of psychiatrists in the management of substance misuse a questionnaire survey

Abstract: Aims and methods A postal questionnairesent to all psychiatrists working in four NHStrusts in and around Birmingham was used to survey the number of new cases of drug and alcohol misuse identified in the previous month and the degree of postgraduate training in the management of such cases. Attitudes and beliefs about substance misuseproblems were also elicited. Results A responserate of 70%wasachieved acrosssix sub-specialities in psychiatry and four levels of training. Of the 143respondents, over half had id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Landy et al (2005) found that 54% of fourth-year medical students in Britain perceived AOD treatment interventions to lack credible evidence. Doubts regarding the efficacy of available treatments or interventions have been identified as detracting from health professionals' willingness to intervene (Borrelli et al, 2001;Day, Arcelus, & Kahn, 1999;Kaner et al, 1999).…”
mentioning
confidence: 99%
“…Landy et al (2005) found that 54% of fourth-year medical students in Britain perceived AOD treatment interventions to lack credible evidence. Doubts regarding the efficacy of available treatments or interventions have been identified as detracting from health professionals' willingness to intervene (Borrelli et al, 2001;Day, Arcelus, & Kahn, 1999;Kaner et al, 1999).…”
mentioning
confidence: 99%
“…13 The constructs of 'role adequacy' (having the necessar y information and skills to identify and respond appropriately) and 'role legitimacy' (the extent to which management of these problems is felt to be the professional's responsibility) have been highlighted as important, 14 and are associated with support and perceived usefulness of education. Proude et al found that individual feedback on performance with education about desired standards is effective in improving the quality of alcohol history taking in junior doctors.…”
Section: Discussionmentioning
confidence: 99%